2005
DOI: 10.2460/ajvr.2005.66.143
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of house dust mite allergens (Der f 1 and group 2) on the skin and hair of dogs

Abstract: Associations exist between environmental HDM allergen concentrations and HDM allergens on the skin and hair samples of dogs. Environmental allergen load is a major factor in accumulation of allergens on the skin and hair of dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Most dogs in the CCAAPS homes were allowed to go out, and could carry outdoor allergens indoors on their feet and fur. Though we did not show that the number of family members was associated with higher Alternaria antigen level, others have shown the transport of cat and house dust mite allergens in human clothing and hair (Almqvist et al, 1999;Randall et al, 2005;Jackson et al, 2005;Karlsson and Renström, 2005). Salo et al (2005) also found a positive association between Alternaria antigen concentration and the presence of dogs.…”
Section: Discussioncontrasting
confidence: 88%
“…Most dogs in the CCAAPS homes were allowed to go out, and could carry outdoor allergens indoors on their feet and fur. Though we did not show that the number of family members was associated with higher Alternaria antigen level, others have shown the transport of cat and house dust mite allergens in human clothing and hair (Almqvist et al, 1999;Randall et al, 2005;Jackson et al, 2005;Karlsson and Renström, 2005). Salo et al (2005) also found a positive association between Alternaria antigen concentration and the presence of dogs.…”
Section: Discussioncontrasting
confidence: 88%
“…to collect the dust samples between the first week of September and the first week of October, as this has been shown to be the time of year with the highest prevalence of HDM at this location 7,34 . The 150 dust samples were collected using a standard technique [11][12][13][21][22][23][24] . Briefly, only the areas identified by the owners as above were sampled.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Several studies have investigated the biology, ecology and allergenic potential of HDMAs in humans and dogs. [8][9][10][11][12][13][14][15] These have informed strategies for allergen avoidance, environmental control and specific immunotherapy used in the management of canine and human AD. The most common HDM species associated with human and canine AD are Dermatophagoides farinae and D. pteronyssinus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centrally heated, well-insulated homes with pets means that allergenic material related to HDM and cats and dogs is common (1,2). Estimates from the Pet Food Manufacturers Association are that approximately 20 % of UK households keep dogs or cats.…”
mentioning
confidence: 99%